2022
DOI: 10.3389/fphys.2022.840065
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Administration of L-Carnitine During the Fattening Period of Early Feed Restricted Lambs Modifies Ruminal Fermentation but Does Not Improve Feed Efficiency

Abstract: Early feed restriction of lambs may program animals to achieve reduced feed efficiency traits as a consequence of permanent mitochondrial dysfunction. The hypothesis at the background of the present study is that dietary administration of L-Carnitine (a compound that promotes the activation and transportation of fatty acids into the mitochondria) during the fattening period of early feed restricted lambs can: (a) improve the biochemical profile of early feed restricted lambs, (b) improve feed efficiency, (c) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 76 publications
0
2
1
Order By: Relevance
“…Dietary LC inclusion did influence the feed intake of the animals during the course of this experiment. The outcome of this work are in contrary with previous investigation indicating no clear impact of LC on DMI in fattening lambs (Martín et al, 2022). A recent study in Ghezel lambs indicated that dietary inclusion of LC up to 1.5 g/day did not alter the feed intake of the animals (Solhjoo et al, 2014).…”
Section: Discussioncontrasting
confidence: 99%
“…Dietary LC inclusion did influence the feed intake of the animals during the course of this experiment. The outcome of this work are in contrary with previous investigation indicating no clear impact of LC on DMI in fattening lambs (Martín et al, 2022). A recent study in Ghezel lambs indicated that dietary inclusion of LC up to 1.5 g/day did not alter the feed intake of the animals (Solhjoo et al, 2014).…”
Section: Discussioncontrasting
confidence: 99%
“…The abundance of Oscillibacter increased, while Phocaeicola and Christensenellaceae_R-7_group significantly decreased with the HR diet ( Wang K. et al, 2021 ). Dietary administration of L -carnitine can improve feed efficiency and modulate the ruminal and intestinal microbiota of lambs, ruminal fermentation was also improved with higher concentration of SCFA were detected ( Martin et al, 2022 ).…”
Section: Diet Improves Meat Quality By Altering Gut Microbiotamentioning
confidence: 99%
“…Many studies have shown that breed, age at slaughter, the feeding system and related muscle development and the proportion of different types of muscle fibers determine important meat characteristics for the consumer, such as color, tenderness, juiciness or intramuscular fat content, as well as the presence of biologically active ingredients [3][4][5][6][7][8][9][10][11]. The quality of the meat is also affected by physiological, biochemical and metabolic changes that occur during meat aging.…”
Section: Introductionmentioning
confidence: 99%